2012
DOI: 10.1111/j.1538-7836.2011.04514.x
|View full text |Cite
|
Sign up to set email alerts
|

Coronary artery calcification score and carotid intima–media thickness in patients with hemophilia

Abstract: To cite this article: Zwiers M, Lefrandt JD, Mulder DJ, Smit AJ, Gans ROB, Vliegenthart R, Brands-Nijenhuis AVM, Kluin-Nelemans JC, Meijer K. Coronary artery calcification score and carotid intima-media thickness in patients with hemophilia. J Thromb Haemost 2012; 10: 23-9.See also Makris M, van Veen JJ. Reduced cardiovascular mortality in hemophilia despite normal atherosclerotic load. This issue, pp 20-2; Biere-Rafi S, Tuinenburg A, Haak BW, Peters M, Huijgen R, de Groot E, Verhamme P, Peerlinck K, Visseren … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 34 publications
3
33
1
Order By: Relevance
“…8 Recently, 2 studies investigated whether hypocoagulability is associated with decreased atherogenesis by evaluating subclinical atherosclerosis and endothelial function in hemophilia patients and in matched unaffected controls. 6,7 The first study, a multicenter study from The Netherlands and Belgium compared 51 hemophilia A and B patients with obesity, as a proxy for increased cardiovascular risk, with 47 normal weight hemophiliacs and healthy age-matched controls with (42) and without (50) obesity. 6 The mean age of the subjects was 50 years and none had previous CVD.…”
Section: Atherosclerosis In Patients With Hemophiliamentioning
confidence: 99%
See 1 more Smart Citation
“…8 Recently, 2 studies investigated whether hypocoagulability is associated with decreased atherogenesis by evaluating subclinical atherosclerosis and endothelial function in hemophilia patients and in matched unaffected controls. 6,7 The first study, a multicenter study from The Netherlands and Belgium compared 51 hemophilia A and B patients with obesity, as a proxy for increased cardiovascular risk, with 47 normal weight hemophiliacs and healthy age-matched controls with (42) and without (50) obesity. 6 The mean age of the subjects was 50 years and none had previous CVD.…”
Section: Atherosclerosis In Patients With Hemophiliamentioning
confidence: 99%
“…6,7 Furthermore, classical cardiovascular risk factors, such as hypertension, seem even more prevalent in hemophilia patients. Indeed, in clinical practice, an increasing number of hemophilia patients are diagnosed with CVD.…”
Section: Introductionmentioning
confidence: 99%
“…13 However, although some clinical trials have shown a reduced incidence of myocardial infarction in patients with hemophilia A, 14,15 others have shown that the degree of atherosclerosis burden, as measured by different modalities such as intima–media thickness, degree of coronary artery calcification, plaque density of large vessels, and mode of endothelial vascular dilatation, is similar to that in the general population. 16,17 Nonetheless, reduced cardiovascular mortality 16,18 has been shown in hemophilic patients and is probably because of reduced fatal occlusive atherothrombosis.…”
mentioning
confidence: 99%
“…Results from clinical studies on the development of atherosclerosis in hemophilic patients using IMT or other imaging techniques were conflicting [74–79], although most studies did not demonstrate a protective effect of hemophilia [74–77]. The inconsistent results from studies comparing IMT of the carotid and femoral arteries of hemophilic patients and controls [77–79] might be attributable to differences in the progression of atherosclerosis between coronary, carotid and femoral arteries.…”
Section: Hypocoagulabilitymentioning
confidence: 99%